Persepsi Pelanggan terhadap Online Branding pada Website Binus University - Meyliana, Meyliana; W., Henry Antonius E.; Santoso, Stephen W. (Bina Nusantara University, 2012)
Implementation of e-marketing or digital marketing help companies compete in the free market. For that, the company needs to obtain information about the customer perception in assessing e-marketing or its digital marketing (website). The research uses digital marketing framework method that consists of several variables, such as attract, engage, retain, learn, relate and online branding in which the hypothesis is tested by correlation analysis and regression analysis. Based on correlation analysis, all the hypotheses of H1 is received (related) and based on regression analysis, all the hypotheses H1 is accepted (effectible).